CFD simulation 3D premixed combustion of methane: influence of the excess air - Vidian, Fajri; Edianto, Fandy; ., Ismail (International Journal of Engineering and Technology, 2019)
Methane is one of the most widely used fuels especially for combustion in gas turbine. The utilization of methane for application in gas burner requires a design step. A part of a design can be done on CFD simulation. This simulation aims to see the mechanism of premixed flame and the influence of excess air on temperature, CO2 and NOX concentrations inside of the gas burner. The 3D computational fluid dynamic was used in this simulation. The combustion reaction was carried out with the spices transport model. The excess air was varied each of 0%, 20%, 40%, and 60%. The simulation results showed the preheat zone occurred at a distance from 0 mm to 300 mm and the reaction zone occurred at a distance above 300 mm in combustion chamber. The increasing of the excess air decreased the temperature distribution as well as the concentration of CO2 and NOX but increased the concentration of O2.Â